Stapedotomy or Stapedectomy: Does It Really Matter? - Francisco Teixeira-Marques; Rita Vaz Osório; Mónica Teixeira; Joana Rebelo; Sandra Gerós; Diamantino Helena; António Faria de Almeida; Pedro Oliveira (International Archives of Otorhinolaryngology)
Introduction Otosclerosis leads to stapes fixation and consequent conductive hearing loss. Surgery is the mainstay of treatment, and it can be achieved through small fenestra stapedotomy or stapedectomy. Despite the first being favored by most, evidence supporting its superiority over the latter remains inconclusive.